Local-Regional Recurrence of Pheochromocytoma/Paraganglioma: Characteristics, Risk Factors and Outcomes - Cui, Yunying; Ma, Xiaosen; Gao, Yinjie; Chang, Xiaoyan; Chen, Shi; Lu, Lin; Tong, Anli (Frontiers in Endocrinology, 2021)
Objective To study the characteristics, risk factors, and outcomes of local-regional recurrence of pheochromocytoma and paraganglioma (PPGL). Methods Clinical data of 96 PPGL patients with local-regional recurrence and 112 patients without recurrence were retrospectively analyzed. Results Recurrent patients exhibited a median recurrence time of 6.0 (4.0, 9.0) years after resection of the primary tumor. SDHB mutation [HR 4.1 (1.7, 9.5), p=0.001), primary tumor size ≥5cm [HR 2.3 (1.1, 4.7), p=0.028], and average Ki-67 count ≥3% in the primary tumor [HR 2.6 (1.4, 4.9), p=0.003] were independent predictors for recurrence of PPGL. Primary tumor sizes ≥5cm [HR 5.1 (1.7, 15.3), p=0.003] and average Ki-67 counts ≥3% of the primary tumor [HR 2.4 (1.1, 5.2), p=0.035] were independent predictors for recurrence of pheochromocytoma, while SDHB mutation [HR 4.6 (1.5, 13.9), p=0.007] was a predictor for paraganglioma recurrence. Among recurrent patients, 47% (45/96) had multiple nodules in recurrent sites, and 58% (56/96) had metastases, with 20% (19/96) being implantation metastases. The risk of metastases (42% vs. 25%, p=0.030) and death (15% vs. 8%, p=0.003) was significantly increased in untreated patients after recurrence compared with treated patients. Conclusion Long-term follow-up is necessary for all PPGL patients. Risk factors for recurrence of pheochromocytoma and paraganglioma differ, with primary tumor size and average Ki-67 count representing independent predictors for pheochromocytoma patients and SDHB mutations predicting paraganglioma recurrence. Although the treatment of recurrence can be difficult, patients should be treated once recurrence is detected as it decreases the risk of metastases and death.